Arda Olla Rangeland Unit Participatory Rangeland Management Plan - Arda Olla Rangeland Community (Arda Olla Rangeland Community, 2024)
This is the rangeland management plan produced by the Arda Olla rangeland community, under participatory rangeland management (PRM), as part of a One Health approach supported by the project HEAL.